Geochronology of Cadmium (Cd), Cuprum (Cu), and Arsenics (As) in Annual Band of Coral Porites lutea at Pantai Kondang Merak, Malang - Luthfi, Oktiyas Muzaky; Rijatmoko, Sigit; Isdianto, Andik; Setyohadi, Daduk; Jauhari, Alfan; Lubis, Ali Arman (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2019)
Coral reef is a massive natural building block that mainly composed of hard coral. In ecological view coral reef is the center of biological activity for shelter, foraging and feeding place. Porites lutea is a common coral in reef flat area such as in Pantai Kondang Merak. This coral can form a massive with hillocky colony surface and has a slow linear extension rate, that made this coral has long longevity. The annual growth band of coral skeleton provide information of pollutants in the coastal extending back over several years ago due to ability of coral aragonite traped trace metal from environment. The aim of this research was to determine the concentration of trace metals of Cd, Cu and As along with the coral annual banding. The heavy metals detection was performed using ICP-OES (iCAP 7400 Series). The concentration of Cd, Cu and As in sample 1 (KM1) were 2.236 mg/kg, 9.726 mg/kg, and 2.474 mg/kg, while sample 2 (KM2) were 1.989 mg/kg, 19.157 mg/kg, and 2,064 mg/kg respectively. Two ways mechanism of trace metals to be trapped in the coral skeleton are by direct mechanism when trace metals in a form dissolved ion that were uptaken by coral then stored into coral skeleton and by indirect mechanism when particulate metals ingested by plankton then eaten by coral through coral tissue. The tracing of heavy metal in coral is provided important information of environment condition of the sea from 2009 - 2015 that may be used for authority decision regarding pollutant ambient in the sea environment.